Pseudo-code: Modelling evaporation in electron-beam physical vapour deposition of thermal barrier coatings - Chevalier, Julie; Isern, Luis; Almandoz Forcen, Koldo; Chalk, Christine; Nicholls, John R. (Cranfield University, 2023)
Pseudo-code for EBPVD ingot evaporation computational model
Keywords: 'Thermal barrier coatings'; 'Electron-beam physical vapour deposition'; 'MATLAB'; 'Modelling'; 'Coatings'; 'Rare-earth zirconates'; 'Aerospace Materials'; 'Synthesis of Materials'; 'Theory and Design of Materials'; 'Ceramics'